2017
DOI: 10.1007/s41783-017-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmosphere Packaging for Mango and Tomato: An Appraisal to Improve Shelf Life

Abstract: In the present study modified atmospheric (MA) packages, having package size of 19 × 19 cm 2 for a fill weight of 500 ± 100 g were developed for the experimental purpose. The storage study of MA packages was performed at 10 ± 1, 18 ± 1 and 27 ± 1 °C temperatures, considering low-density polyethylene (LDPE) packaging film with 0.1, 0.05, 0.025 and 0.0125% perforations. The performance of film packages was evaluated for their ability to establish equilibrium condition at target levels and to extend the shelf lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Avocado membrane structure is made up of mainly cellulose and hemicellulose, as well as pectins; hydrolysis and depolymerization of these structures by enzymes such as polygalacturonase and pectin methylesterase results in fruit softening (Bower and Cutting, 1988). Dhalsamant et al (2017) reported that the use of modified atmosphere packaging with O 2 (2%) and CO 2 (10%) delayed ripening and softening in mango fruit. In this study, it could be argued that coating fruit with GA 15% + M, CMC 1% + M, and GA 10% + M resulted in a modified atmosphere with reduced O 2 and increased CO 2 levels, causing a reduction of enzymatic activities in coated avocados compared with uncoated avocados.…”
Section: Resultsmentioning
confidence: 99%
“…Avocado membrane structure is made up of mainly cellulose and hemicellulose, as well as pectins; hydrolysis and depolymerization of these structures by enzymes such as polygalacturonase and pectin methylesterase results in fruit softening (Bower and Cutting, 1988). Dhalsamant et al (2017) reported that the use of modified atmosphere packaging with O 2 (2%) and CO 2 (10%) delayed ripening and softening in mango fruit. In this study, it could be argued that coating fruit with GA 15% + M, CMC 1% + M, and GA 10% + M resulted in a modified atmosphere with reduced O 2 and increased CO 2 levels, causing a reduction of enzymatic activities in coated avocados compared with uncoated avocados.…”
Section: Resultsmentioning
confidence: 99%
“…Film packaging with an modified atmosphere has been widely used in fruit and vegetable storage (Wilson et al, 2019). Modified atmosphere packaging maintains a balance between fruit respiration and the air permeability of packaging films, which forms a microenvironment with high CO 2 but low O 2 so that inhibits the metabolism of fruits and vegetables and retains freshness for extended shelf life (Dhalsamant et al, 2017;Chen et al, 2019). However, as the primary packaging materials, gas permeability of PE films is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Modified atmosphere packaging (MAP) is a novel technology that can control gas composition inside the package to maintain freshness and extend the shelf life of fruits and vegetables. Highly respiring produce requires modification of the O 2 and CO 2 levels in packaging. Gas composition changes within the packaging film depend on various factors such as the weight of the produce, respiration rate, package size, and gas permeability of the film. By controlling the gas composition, MAP effectively reduces the respiration rate and dehydration of fresh fruits and vegetables, thus retarding deterioration and extending the shelf life. Plastic films with an oxygen transmission rate (OTR) of over 10,000 cm 3 /m 2 ·d can induce a desirable modified atmosphere within fresh produce packaging throughout the storage period …”
Section: Introductionmentioning
confidence: 99%
“…Gas composition changes within the packaging film depend on various factors such as the weight of the produce, respiration rate, package size, and gas permeability of the film. 5 8 By controlling the gas composition, MAP effectively reduces the respiration rate and dehydration of fresh fruits and vegetables, thus retarding deterioration and extending the shelf life. 9 11 Plastic films with an oxygen transmission rate (OTR) of over 10,000 cm 3 /m 2 ·d can induce a desirable modified atmosphere within fresh produce packaging throughout the storage period.…”
Section: Introductionmentioning
confidence: 99%